Analisis Tingkat Kepuasan Konsumen Dalam Menggunakan Layanan Pengiriman Barang Pada J&T Express Kabupaten Nias Barat - Elfan Selamat Putra Gulo; Eduar Baene; Palindungan Lahagu; Martha Surya Dinata Mendrofa (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
This study aims to determine the analysis of consumer satisfaction in using goods delivery services on J&T Express in West Nias Regency. This study is a descriptive research with qualitative approach with J&T Express research object of West Nias Regency. Data sources are taken from documentation, interview results and observation results. In this study, interviews with various questions on research topics were conducted directly. The results of the study show that consumers are less satisfied in the services provided by J&T Express Nias Barat in terms of delivery services and delivery of goods to direct consumer addresses, where many consumers complain whether it is delay in delivery of goods, damage to goods, couriers making unilateral cancellation of goods or errors of delivery that become an evaluation material for J&T's own services so that the service provided to consumers is even better.